Assessing Proactive Investigation Techniques Against Corruption: A Comparative Study of Indonesia, the United States, Hong Kong, and Singapore - Lutfiasandhi, Kristiya; Dian Ningtias, Ayu; Sintia Putri, Dewi Ajeng (Universitas Islam Lamongan, 2026)
The Indonesian Criminal Procedure Code (KUHAP) does not formally recognize the term Operasi Tangkap Tangan (OTT) or